2019
DOI: 10.5539/jas.v11n17p11
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Soil on the Traction Performance of a 65 kW MFWD Tractor

Abstract: This study aimed to investigate the influence of the mechanical behaviour of the soil surface on the traction performance and the fuel consumption of an agricultural tractor, both in qualitative and in quantitative terms, in order to increase the consciousness about the major role of the soil mechanical response in the optimisation of the energy aspects involved in the traction developed by a tractor and promote the development of new strategies to reduce costs of tillage management and improve agricultural su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The study of traction efficiency is given in [1][2][3][4], where there is a significant effect of the radial load and internal pressure in the tire on the performance of tractors. The authors [1][2][3][4] note the positive effect of reducing the internal pressure from 160 kPa to 60 kPa, which is manifested in a decrease in fuel consumption to 14-16 %, an increase in traction properties by 12-30 % (at a constant tractor weight). In works [1][2][3][4], a positive effect was found during the operation of tractor tires in terms of internal pressure close to the lower limit -60 kPa.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study of traction efficiency is given in [1][2][3][4], where there is a significant effect of the radial load and internal pressure in the tire on the performance of tractors. The authors [1][2][3][4] note the positive effect of reducing the internal pressure from 160 kPa to 60 kPa, which is manifested in a decrease in fuel consumption to 14-16 %, an increase in traction properties by 12-30 % (at a constant tractor weight). In works [1][2][3][4], a positive effect was found during the operation of tractor tires in terms of internal pressure close to the lower limit -60 kPa.…”
Section: Methodsmentioning
confidence: 99%
“…The authors [1][2][3][4] note the positive effect of reducing the internal pressure from 160 kPa to 60 kPa, which is manifested in a decrease in fuel consumption to 14-16 %, an increase in traction properties by 12-30 % (at a constant tractor weight). In works [1][2][3][4], a positive effect was found during the operation of tractor tires in terms of internal pressure close to the lower limit -60 kPa. But the authors of [5] point to a positive effect manifested in the improvement of the environmental performance of modern tires with a decrease in pressure from 80 kPa to the recommended 60 kPa and predict its further improvement with a decrease in internal pressure to 40 kPa.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, researchers have increasingly used various methods for modeling rolling resistance, traction and other indicators of tractors and machines [4][5][6]. Nevertheless, obtaining a tractor power balance in the field, using modern sensors and a new generation of recording equipment, allows a more objective assessment of the processes occurring in the machine-transmission-tire-soil system [7][8][9] It is well known that the power balance of any mobile power tool moving uniformly on a horizontal surface can be written as follows:…”
Section: Introductionmentioning
confidence: 99%
“…However they also reported that only at a tire pressure of 160 kPa and a slip of less than 15% is a reduction in specific fuel consumption achieved. An increase in tire pressure from 60 kPa to 160 kPa resulted in an increase in specific fuel consumption of up to 16% [10]. Ekinci et al [11] experimentally investigated the effects of three different tread profile heights, axle load and inflation pressures of a radial tire on the traction performance.…”
Section: Introductionmentioning
confidence: 99%